2017
DOI: 10.1007/s10926-017-9730-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Sickness Absence and Return to Work Among Employees with Common Mental Disorders: A Scoping Review

Abstract: Purpose To present an overview of the existing evidence on prognostic factors of (recurrent) sickness absence (SA) and return to work (RTW) among workers with a common mental disorder (CMD). This scoping review provides information about determinants for SA and RTW, which could be used to develop better interventions aimed at the prevention of SA and promotion of RTW among workers with a CMD. Methods Relevant articles were identified in PubMed, Embase, PsycINFO, PSYNDEX, and SINGLE up to October 2016. In order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
195
3
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(225 citation statements)
references
References 110 publications
12
195
3
15
Order By: Relevance
“…In all groups, participants who scored high on KEDS and/or MADRS-S had longer net sick leave than those who had low scores on these instruments. The same pattern has been found in previous studies (1,16,29,34,35,53), which suggests that symptom severity may be the factor with the greatest influence on length of sick leave.…”
Section: Comparison Of Current Study Results With Those Of Previous Ssupporting
confidence: 88%
See 1 more Smart Citation
“…In all groups, participants who scored high on KEDS and/or MADRS-S had longer net sick leave than those who had low scores on these instruments. The same pattern has been found in previous studies (1,16,29,34,35,53), which suggests that symptom severity may be the factor with the greatest influence on length of sick leave.…”
Section: Comparison Of Current Study Results With Those Of Previous Ssupporting
confidence: 88%
“…In summary, some have found an association between specific psychiatric diagnoses such as depression (33) and anxiety (1) and long-term sick leave. Others have found that the severity of symptoms of anxiety and distress is the most important factor associated with longer sick leave (1,16,29,34,35). This study provides an opportunity to examine the results of independent structured psychiatric interviews and self-rated symptom severity assessments in a population of patients on sick leave for common mental disorders.…”
mentioning
confidence: 87%
“…For young professional employees, aspects of the psychosocial work environment seem to be of importance for their mental health. Several studies and reviews have found that that high-strain jobs, characterized by low employee control and high demands, are associated with lower well-being and higher stress levels [18][19][20][21][22][23] and also associated with sick leave from work [24][25][26][27][28]. However, employees' attitudes towards the job is also of importance for their well-being.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons underlying SA are, apart from disease or injury, likely to involve a combination of different factors including stress and strain in the workplace and poor recovery. Previous research has identified and investigated various risk factors for SA, such as being a woman, older age, high job demands, and a low socioeconomic status (Allebeck and Mastekaasa 2004; Mather et al 2015; Vries de et al 2017). So far, fewer studies have investigated time pressure, including overtime work, as well as sleep disturbances, despite these having the potential of being important risk factors for SA.…”
Section: Introductionmentioning
confidence: 99%